2023
DOI: 10.1002/adfm.202212394
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization‐Induced Enhanced Electrochemiluminescence from a New Tris(bipyridine)ruthenium(II) Derivative

Abstract: Classic tris(bipyridine)ruthenium(II) complex (Ru‐bpy) with high electrochemiluminescence (ECL) efficiency still suffers from a serious aggregation‐caused quenching (ACQ) problem, which greatly weakens its ECL efficiency to restrict further applications in solid‐state ECL imaging and light‐emitting devices. Herein, the crystallization‐induced enhanced ECL (CIE‐ECL) of tris(bipyridine)ruthenium(II) derivatives (Ru‐TPE) are reported by decorating Ru‐bpy with inherent aggregation‐induced emission active tetraphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The emission spectrum of excimer emission is relatively broad, thus resulting in wider red‐shifted peaks in ECL spectra [27] . The four architectures with different stacking patterns exhibited similar ECL emissions, and their substantially red‐shifted ECL peaks indicated that the excited states in different stacking patterns might be governed by the mechanism of surface state transitions with lower energy rather than the band gap [19b,28] . In addition, the results were influenced by analyte concentration as well as instrument slit width and resolution [29] .…”
Section: Resultsmentioning
confidence: 96%
“…The emission spectrum of excimer emission is relatively broad, thus resulting in wider red‐shifted peaks in ECL spectra [27] . The four architectures with different stacking patterns exhibited similar ECL emissions, and their substantially red‐shifted ECL peaks indicated that the excited states in different stacking patterns might be governed by the mechanism of surface state transitions with lower energy rather than the band gap [19b,28] . In addition, the results were influenced by analyte concentration as well as instrument slit width and resolution [29] .…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure S2 in the Supporting Information, an obvious diffraction peak at 12.381°corresponding to the preferential (140) growth plane was observed in the X-ray diffraction (XRD) pattern of Ru-TPE NSs, which was consistent with its simulated signals and Ru-TPE aggregates without bovine serum albumin (BSA). [36] Meanwhile, no new diffraction peaks were detected in the XRD pattern of NSs. The results indicated that BSA may serve as the capping agent to wrap on the Ru-TPE NSs and not participate in the crystallization process to achieve new crystals.…”
Section: Characterization Of Ru-tpe Nssmentioning
confidence: 97%
“…In the previous work, our group reported the visual ECL imaging of a new TPE-decorated tris(bipyridine)ruthenium(II) derivative crystal (Ru-TPE crystal). [36] Nevertheless, the Ru-TPE crystal cannot be suitable for biological assays and clinical applications in the ECL realm because of its large block size and poor dispersibility (Figure S1, Supporting Information). Herein, the ultrathin Ru-TPE nanosheets (Ru-TPE NSs) were obtained by a protein-assisted self-assembly strategy, which exhibited unique AIECL property and good water-dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Zhu and co-workers created a [Ru(bpy) 3 ] 2 + derivative Ru-TPE, incorporating the AIE-active tetraphenylethene (TPE) group. [44] The resulting compound exhibited strong CIECL driven by the TPE group that overcame the inherent ACQ nature of [Ru(bpy) 3 ] 2 + . The authors observed an increased crystallinity of the Ru-TPE crystals compared to plain crystals of [Ru(bpy) 3 ] 2 + , confirmed by pXRD measurements.…”
Section: Crystallization-induced Electrochemiluminescence (Ciecl)mentioning
confidence: 99%